Gender Differences in Decision-making and Leadership: Evidence from Armenia - Diana Minasyan; Gayane Tovmasyan (Business Ethics and Leadership)
This paper summarizes the arguments and counterarguments within the scientific discussion on the issue of gender differences in decision-making and leadership positions. The main purpose of the research is to find out if there are gender differences in decision-making styles, career development, and leadership and reveal the main causes. A systematization of literary sources on the issue of gender differences in the decision-making process indicates that there are real differences: women are more sensitive, men are overconfident, men tend to be leaders more than women. Investigation of the topic proves that in leadership positions men are promoted more than women are, also there is a payment gap between genders. Analysis in the paper is carried out in the following logical sequence: the statistical data available has been analyzed, and then a survey is done, which reveals some issues of gender differences in leadership and decision-making in workplaces in Armenia. Based on the generalization of the results, the differences in decision-making are determined and the corresponding conclusions are drawn. Methodological tools of the research methods were analysis and synthesis of the available data, survey, and statistical methods: cross-tabulation with Pearson Chi-square testing, which proves that there are significant relationships between some factors. The paper presents the results of an empirical analysis, which shows that in Armenia women and men make decisions differently, women have less opportunities for career promotion. The survey reveals that women make decisions in groups, men – alone. The main characteristics of women during the decision-making process are: analytical thinking, consulting, honesty and intuitive thinking. Also, the workers, lower and middle-level managers make decisions mainly in groups, high-level managers – alone. The survey also reveals the main reasons why men are appointed to leadership positions and the main stereotypes that hinder women’s career advancement. The results of the research can be useful for state bodies, labor market, organizations, educational institutions, researchers, etc.